IMPROVING STUDENTS WRITING ABILITY ON PROCEDURE TEXT BY USING FLASH CARD - Purnama, Ratna; Sada, Clarry; ., Sumarni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstract: The title of this research is improving students writing ability on procedure text by using flash card to the seventh grade students of SMP Negeri 1 Sekadau Hulu. The purpose of this research is to improved students writing ability on procedure text. The methode ofthisresearch is classroom action research.Subject of this research is seven grade students class A, consisting 26 students. The result of the research shows that the flash card improved students writing ability on procedure text.The mean score of students increased from 64,13 to 70,77. The average persentage from the first cycle to the second cycle was 67,45.The students are enthusiastic, interested, and motivated to write procedure text by using flash card. Key words: Flash Card, CAR, Writing Ability. Abstrak :Judul penelitian ini adalah meningkatkan siswa dalam menulis teks prosedur dengan menggunakan flash card di SMP Negeri 1 SekadauHulu kelas tujuh. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan siswa dalam menulis teks prosedure. Metode penelitian yang digunakan adalah penelitian tindakan kelas. Subjek penelitian adalah 26 siswa kelas tujuh SMP Negeri 1 Rawak Hulu. Hasil dari penelitian ini menunjukkan bahwa flash card meningkatkan kemampuan siswa dalam menulis teks prosedur.Nilai rata-rata siswaberkisardari 64,13sampai 70,77. Persentase rata-rata darisiklus 1 kesiklus 2 adalah 67,45. Siswasangatantusias, tertarik, dantermotivasiuntukmenulisdenganpenggunaan flash card. Kata kunci : Flash card, PTK, Kemampuan menulis.